FEATURES OF THE COURSE AND TACTICS FOR THE MANAGEMENT OF PATIENTS WITH DYSPLASTIC CONDITIONS OF THE CERVIX DUE TO VAGINAL MICROBIOCENOSIS DISORDERS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Определить оптимальную тактику ведения и изучить особенности ведения пациенток с диспластическими изменениями шейки матки, выявленными на ранних стадиях скрининга шейки матки на фоне бактериального вагиноза и ИПВ-инфекции.